Feminizing Glinda as the Femme Fatale in Wicked (2024) - Perkasa, Adam Yudha (Journal of Indonesian Literacy and Indigenous Culture, 2025)
This research aims to analyze the femininity of the femme fatale in Wicked (2024) directed by Jon M. Chu, with a focus on Glinda as the femme fatale that is analyzed through her depiction in Wicked (2024). Utilizing the theory of male gaze by Laura Mulvey (1975), the goal of this study is to understand the depiction of women in movie, especially Glinda as the femme fatale, that is connected with the social expectation as well as the influence of the femme fatale towards the other character in the movie, This study explores the concept of embracing femininity in women and using it as power instead of seeing it as a weakness in order to influence other people and reach their goal.